The Relationship between Macroeconomic Variables and ISE Industry Index - Ozcan, Ahmet (International Journal of Economics and Financial Issues, 2012)
In this study, the relationship between macroeconomic variables and Istanbul Stock Exchange (ISE) industry index is examined. Over the past years, numerous studies have analyzed these relationships and the different results obtained from these studies have motivated further research. The relationship between stock exchange index and macroeconomic variables has been well documented for the developed markets. However, there are few studies regarding the relationship between macroeconomic variables and stock exchange index for the developing markets. Thus, this paper seeks to address the question of whether macroeconomic variables have a significant relationship with ISE industry index using monthly data for the period from 2003 to 2010. The selected macroeconomic variables for the study include interest rates, consumer price index, money supply, exchange rate, gold prices, oil prices, current account deficit and export volume. The Johansen’s cointegration test is utilized to determine the impact of selected macroeconomic variables on ISE industry index. The result of the Johansen’s cointegration shows that macroeconomic variables exhibit a long run equilibrium relationship with the ISE industry index. Keywords: Macroeconomic variables; ISE industry index; Johansen’s Cointegration Analysis JEL Classifications: G10; G21; E44